CLAIMED CITIZENSHIP ON SOCIAL PROJECTS: THE CASE OF “GORDINHO´S” BODYBOARDING SCHOOL (Fiep Bulletin - online, 2014)
A study conducted with the objective to verify if , in cases of representations of participants on social projects, there are indications of claimed citizenship. The study analyses the results of data produced by 12 semi-structured interviews with the project participants . The results obtained were interpreted by a Critical Discourse Analysis. There were indications of rights to claimed citizenship after identification of some characteristics present on the discourses which demonstrated the degree of commitment, and the identification of the interviewees with what they say . However, part of the discourse reveals extremely objective representations which provide clues that the discourses are permeated by ideological opinions present in society understanding.
Keywords: Claimed citizenship; social projects; physical education